DECISION SUPPORT SYSTEM DETERMINING THE LEVEL OF PUBLIC SATISFACTION OF THE CITY WITHOUT SLUMS PROGRAM (KOTAKU) IN PNPM MANDIRI IN DELI SERDANG DISTRICT USING THE MULTI-ATTRIBUTE UTILITY THEORY METHOD - Syahputra, Prayogo (UIN Sumatera Utara, 2019)
Abstract To evaluate the success of the Kotaku program (City Without Slums) in PNPM Mandiri in Deli Serdang Regency, a study is needed to determine the level of community satisfaction with the results of the Kotaku program. Then in this study, a decision support system will be built to assist in determining the level of community satisfaction with the Kotaku program. The method chosen to support the above problem solving is Multi-Attribute Utility Theory (MAUT). The system design is done by using Unified Modeling Language (UML) modelling and accompanied by a system interface design. The advantage of this system is that it can perform calculations very quickly and effectively. This decision support system shows that with the advancement of science and technology it can help in determining the right level of community satisfaction by following the correct considerations and calculations. But there are still some weaknesses of the system including this system has a simple interface and does not have the feature to backup the database.